2019
DOI: 10.4174/astr.2019.96.3.116
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as an independent predictive factor for pathologic complete response after neoadjuvant chemoradiation in rectal cancer

Abstract: Purpose The predictive role of obesity on pathologic complete response (pCR) after neoadjuvant chemoradiation (nCRT) in rectal cancer remains controversial. This study aimed to evaluate the association between obesity and pathologic response in patients with rectal cancer following nCRT. Methods A total of 320 patients with primary rectal cancer who underwent curative resection after nCRT between January 2010 and September 2014 were enrolled in this study. Obesity was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
3
9
2
1
Order By: Relevance
“…11,[22][23][24] A BMI cut-off point of ≥25 kg/m 2 was used to categorize obesity in our cohort, which is also consistent with prior studies. [25][26][27] Recently, a meta-analysis has shown specifically in rectal cancer, patients with a BMI≥ 25 were found to have significantly better overall survival…”
Section: Discussionmentioning
confidence: 99%
“…11,[22][23][24] A BMI cut-off point of ≥25 kg/m 2 was used to categorize obesity in our cohort, which is also consistent with prior studies. [25][26][27] Recently, a meta-analysis has shown specifically in rectal cancer, patients with a BMI≥ 25 were found to have significantly better overall survival…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Lee et al recently reported obesity as an independent negative predictive factor for complete response to CCRT in rectal cancer. 35,36 As we known, tumor response could reflects early response to treatments and related to late response outcomes including recurrence and survival. Many studies also indicate that obesity is a common risk factor for cardiovascular disease and is an indicator of poor prognosis in multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Hinsichtlich des Einflusses einer Adipositas auf eine neoadjuvante Radiochemotherapie beim lokal fortgeschrittenen Rektumkarzinom zeigen sich inkonsistente Ergebnisse. Eine aktuelle Publikation von Lee et al mit 320 eingeschlossenen Patienten beschreibt eine höhere Rate vollständiger Remission bei übergewichtigen Patienten (25,3 % BMI > 25 kg/m 2 vs. 11,4 % BMI < 25 kg/m 2 ) [37], wohingegen andere Untersuchungen das Gegenteil mit niedrigeren Komplettremissionsraten und seltenerem Schließmuskelerhalt beschreiben. Eine Untersuchung mit 522 Patienten, die bei lokal fortgeschrittenem Rektumkarzinom eine neoadjuvante Radiochemotherapie und anschließende OP erhielten, zeigte hinsichtlich des Downstagings (31,8% BMI > 30 kg/m 2 vs. 60,2% BMI < 30 kg/m 2 ) und der Tumorregression, dass adipöse Patienten schlechter auf die Therapie ansprachen [38].…”
Section: Kolorektales Karzinomunclassified